Regenerasi Kelompok Kesenian karawitan Laras Budaya untuk Pemuda di Desa Bligo, Magelang - Estu Ari Nugroho; Alvina Yusarianti; Nur Arif Anandhita (TAMUMATRA, 2024)
This article aims to identify the regeneration process undertaken by the Laras Budaya Karawitan Art Group in Bligo Village, Ngluwar, Magelang Regency, Central Java. Traditional arts such as karawitan should ideally be utilised to preserve this musical heritage. Karawitan is a traditional music performance involving the use of gamelan instruments. The Laras Budaya Karawitan Art Group, established in 1976 and led by Temu Riyadi, represents this musical tradition in Bligo Village. The regeneration of members within this art group has significantly contributed to preserving karawitan in Bligo Village. Data collection was focused on research needs and employed qualitative techniques. A qualitative methodology was used to explain the phenomena under study comprehensively. Based on observations and research conducted, it was found that the regeneration process by the Laras Budaya Karawitan Art Group has been successful. This is evidenced by the forming a karawitan group of youth from Bligo Village aged 18 to 25. The regeneration was carried out through training sessions directly supervised by Indonesian Institute of the Arts (ISI) Yogyakarta students. The training method employed in this regeneration process was the demonstration method, enabling the youth to grasp the material effectively.